Studies in Information Technology Applications (SITA) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Studies in Information Technology Applications (SITA) is a gender empowerment project sponsored by infoDev.